Corporate Governance of Small-and-Medium Sized Commercial Banks in China - Ziwen Yin (Journal of World Economy, 2023)
Small-and-medium sized commercial banks have developed significantly along with China’s economic development, but in this process, there are often problems; the fundamental reason lies in need for a severe internal governance system and governance capacity of small-and-medium sized commercial banks. Given this situation, this paper focuses on the study of corporate governance of small-and-medium sized commercial banks. Then it takes targeted optimization measures to address its shortcomings to enhance the comprehensive governance level of small-and-medium sized commercial banks, improve their market competitiveness, and lay a good foundation for their long-term sustainable development.